(untitled) (Agrometeoros, 2020)
Climate services are scientifically based products that enhance users’ understanding on the impacts of climate on their decisions and actions. Decision Support Systems (DSSs) are programs that use models and other information to make site-specific recommendations for farm management-related activities. Climate variability is a source of production risk worldwide and is associated with other risks such as pest and disease incidence. Extreme climate events such as drought, intense precipitations, and pest or disease outbreak can also affect commodity prices and increase marketing risk. However, climate forecasts alone usually do not provide actionable information for improving decisions and policy. Climate forecasts are the basis for co-development of DSSs to support improved decisions at different scales to maximize profits and input use, and to minimize climate risks, and negative environmental externalities. Major advances in developing DSSs occurred through design, diffusion, and adoption made possible through continuous interaction among scientists, boundary organizations and end users in a participatory research and development process. This article describes the evolution of this process and addresses issues of co-development, participation, scale, and future research needs through a case study that highlights commonalities and differences between producer needs, perceptions, and adoption at two research sites (one in Florida, USA and the other in southeastern Paraguay).